Swedish Archaeologist Prof. Dr. Axel Waldemar Persson’s Studies in Türkiye - Gülşah Eser; Kubilay Arpacı (Yakın Dönem Türkiye Araştırmaları)
Prof. Dr. Axel Waldemar Persson (1888-1951) was a leading name in the field of archaeology with his archaeological excavations and academic studies. Persson, who had been excavating various parts of Greece since the 1920s, obtained excavation permission in Türkiye with the decree in 1935 signed on the basis of the reference of Gustaf VI Adolf, Crown Prince of Sweden. In this context, Persson carried out drilling works in Milas Genciktepe in order to find traces of the Carian civilization, and with the decree in 1936, he took the management of the Genciktepe Excavation. In order to protect and exhibit the finds from this excavation, the request to convert the Milas Firuz Bey Mosque into a museum was raised with Persson’s initiatives in 1938. In the following period, his studies in Türkiye were interrupted with the beginning of World War II. Persson returned to Türkiye with the Labraunda Excavation in 1948 and continued to work as the head of the excavation until his death.This study aims to examine his works in Türkiye in a holistic way, based on the information obtained from the literature review, as well as archival documents and the national press. The research has concluded that Persson wanted with his archaeological excavations in Genciktepe and Labraunda to prove his understanding that the civilizations that had ruled in the Aegean during the Prehistoric period had had a common culture.